(untitled) (CAHIERS MAGELLANES-NS, 2024)
The evolution in Artificial Intelligence technology enables the integration of AI systems into various fields. Education and research are some of the fields that use Chatbots more effectively. A new era of education and research based on these Chatbots and artificial intelligence. This technology is quickly growing and is increasingly used for educational and research purposes. Chatbot technology has the potential to provide quick and personalized services through the concept of a virtual assistant that replicates humanized conversation to everyone including educators, students, and researchers. In this perspective, Chatbots can also act as virtual teaching assistants, supporting educators by providing immediate support by answering questions, offering explanations, and providing additional resources. However, the application of these advanced systems is associated with several challenges and limitations, mainly related to quality, ethics, and legal issues. Using the AI generated data without any referrals, affects the quality of education and research. Thus, there is a high need for analysis of the usage of Chatbots in the field of education and research. Thus, this research focuses on a detailed study of Chatbots, an overview of chatbot technology, the use of Chatbots in education and research, benefits, and limitations. For the betterment of quality in education and research, this paper is extended to the way Chatbots are misused and manipulated in the field of education and research. It also proposes effective solutions to the observed ethical dilemmas.